Spatial-based cooperative transmission power assignment for mobile telecommunication systems. (September 2016) - Ahmed, Zinah Rafea; Subramaniam, Shamala; Zukarnain, Zuriati; Othman, Mohamed
Transmission power allocation in modern mobile telecommunication systems is one of the most important aspects affecting overall performance. Addressing this issue has huge impact on improving state-of-the-art for mobile telecommunication systems such as Long Term Evolution—Advanced by reducing inter-cell interference. To approach global optimality, some sort of cooperation between base stations is needed to overcome many shared limitations. This article proposes cooperative transmission power assignment mechanism based on the coordinated multiple points' concept. It provides mathematical treatment and technical development for the proposed solution. This solution works in distributed fashion which is one of the main strengths of our approach. The proposed transmission power mechanism adopts auction theory approach to allocate power level for each base station. The proposed solution has showed tremendous good performance in extensive simulation experiments.